The longer-term effects of IVF on offspring from childhood to adolescence - Hart, R. J.; Wijs, L. A. (Frontiers in Reproductive Health, 2022)
It is well established that there are increased pregnancy-related complications for a woman who conceives through assisted reproductive treatment (ART). Furthermore, it is known that the risk to the child born is greater, believed to be related to prematurity and growth restriction. Studies have also reported epigenetic changes in the DNA of offspring conceived through ART. In addition, it is believed that they have a greater risk of congenital malformations, although some of these risks may relate to underlying infertility, rather than the ART treatment per se. As a result, it may be expected that there is a greater risk to the longer-term health of the child who is born from ART; however, evidence about the long-term health of children conceived through ART is reassuring. Even though, it is recognised that many of the studies in this field come with limitations. Low numbers of participants is one of the major limitations, which makes subgroup analyses for diverse types of ART, or diverse types of infertility, not feasible. Furthermore, studies are often limited by short follow-up periods because of the difficulty and costs involved in longitudinal study designs. In addition, the rapid changes over time in ART limit the generalisability and significance of long-term findings. Well-designed studies investigating the long-term health outcomes of ART-conceived offspring and the potential influences of various aspects of the ART procedure, as well as studies of the potential underlying epigenetic mechanisms, are imperative. Furthermore, conclusions from childhood hospitalisation data from the United Kingdom, the long-term follow-up and quality of life study from researchers in Melbourne, and the data published from the Western Australian Growing Up Healthy Study will go a long way to help reassure current and prospective parents who may require ART to conceive.